Primary and secondary reinforcements in reinforced concrete corbels - Rezaei, Mehdi; Osman, Siti Aminah; Shanmugam, Nandivaram E. (Journal of Civil Engineering and Management, 2013)
The study is concerned with normal-strength concrete corbels. 30 such corbels were studied by finite element modelling and the variables considered include ratios of primary and secondary reinforcement, type of applied loading, vertical or horizontal. Finite element modelling with a software package LUSAS was used to analyse four series of corbels namely PV series (primary reinforcement with vertical loading), SV series (secondary reinforcement with vertical loading), PH series (primary reinforcement with horizontal loading) and SH series (secondary reinforcement with horizontal loading). The results indicate that corbels with neither primary reinforcement nor secondary reinforcement fail suddenly. In the case of PV series and SV series, corbels increase in ratio of primary and secondary reinforcement generally resulted in enhancement of strength and ductility when subjected to only vertical loading. This increase is significant up to 0.4% in the case of primary reinforcement and 0.3% in the case of secondary reinforcements. No noticeable change in ultimate load or ductility was observed for corbels in PH series and SH series. First published online: 24 Oct 2013